DAPATKAH MEDIA JEJARING SOSIAL MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS TEKS EKSPOSISI? - Trisna Adi Pratama (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
Abstract - This study aims to test the effectiveness of a model of learning as an alternative to help the problem of learning to write exposition text. Learning model in this research is participatory model assisted social networking media, especially instagram and line. The population of this study were all students of SMA Negeri 15 Bandung in the academic year 2017/2018 consisting of nine classes. The sample of this research consisted of experimental class which represented by X MIPA 3 and control class represented by X MIPA 1, each class amounted to 26 students. The sampling technique in this research is purposive sampling technique. The method used in this research is an experimental method using a quantitative approach. The design of this research uses the design of The Matching-Only-Pretest-Posttest Control Group Design. Data collection techniques in this study include test techniques, field notes, and questionnaires. After the research and data were analyzed, the average value of pretest of the experimental class was 74 and the mean value of the experimental class posttest was 82. The average value of the control class pretest was 76 and the mean value of the control class posttest was 78. Later data obtained, processed or analyzed using SPSS statistics 20. Based on the statistical calculations obtained Asymp value. Sig. (2-tailed) by 0.049 <α = 0.05. That is, H1 is accepted. Thus, the ability of the experiment class students is significantly higher than the control class. That is, the participatory model of media-assisted instagram social media is more effective than participatory model assisted by social networking media line. Keywords: participatory model, social networking media, instagram, line, learning writing exposition text